Electrical Resistivity Survey for Groundwater Investigation in Parts of Osun State, Southwestern Nigeria - Adebayo, A. S.; Dasho, O. A.; Olufemi, A. P.; Babatunde, O. A.; Oghenenyovwe, O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study used a non-invasive, cost-effective geophysical method for locating suitable sites for groundwater development. Thirty-two Vertical Electrical Sounding (VES) were probed in the investigated area using Schlumberger array. The data acquired were interpreted using the partial curve matching technique and computer-aided iteration through WINRESIST. The aquifer properties such as transverse resistance, longitudinal conductance, hydraulic conductivity and transmissivity were computed from the primary geoelectric parameters. The results of the study revealed that the investigated area is marked by heterogeneous lithology with three to five geoelectric layers. The aquifer resistivities ranged from 18 to 318 Ωm while the aquifer thicknesses ranged from 1.7 to 46.2 m. The computed transverse resistance revealed the groundwater development in the investigated area as low/moderate. Also, the transmissivity values computed from the primary aquifer parameters revealed that 72% of the investigated area has low aquifer transmissivity, while 28% have moderate aquifer transmissivity. This implies that the investigated area has low/moderate water-bearing potentiality. The quantitative analysis of the aquifer protective rating revealed that 78.1% of the investigated area has a good natural ﬁlter. Based on the aquifer potential rating and the protective capacity, VESes 10-12, 16, 19-20, 23-25 were recommended for drilling sites. The result of this study provides some important conclusions for future groundwater exploration and management in the investigated area.